'It just wasn't going to be heard': A mixed methods study to compare different ways of involving people with diabetes and health‐care professionals in health intervention research. (1st May 2020) - Racine, Emmy; Riordan, Fiona; Phillip, Eunice; Flynn, Grainne; McHugh, Sheena; Kearney, Patricia M.
Abstract: Background: Guidelines recommend involving intervention users in the intervention development process. However, there is limited guidance on how to involve users in a meaningful and effective way. Objective: The aim of this Study within a trial was to compare participants' experiences of taking part in one of three types of consensus meetings—people with diabetes‐only, combined people with diabetes and health‐care professionals (HCPs) or HCP‐only meeting. Design: The study used a mixed methods convergent design. Quantitative (questionnaire) and qualitative (observation notes and semi‐structured telephone interviews) data were collected to explore participants' experiences. A triangulation protocol was used to compare quantitative and qualitative findings. Participants: People with diabetes (recruited via multiple strategies) were randomly assigned to attend the people with diabetes or combined meeting. HCPs (recruited through professional networks) attended the HCP or combined meeting based on their availability. Results: Sixteen people with diabetes and 15 HCPs attended meetings, of whom 18 participated in a telephone interview. Participants' questionnaire responses suggested similar positive experiences across the three meetings. Observation and semi‐structured interviews highlighted differences experienced by participants in the combined meeting relating to: perceived lack of common ground; feeling empowered versus undervalued; needing to feel safe and going off task to fill the void. Conclusions: The qualitative theme 'needing to feel safe' may explain the dissonance (disagreement) between quantitative and qualitative data. In this study, involving patients and HCPs simultaneously in a consensus process was not found to be as suitable as involving each stakeholder group separately.